Exploring the Effects of Oxidative Stress on Female Reproductive Function: The Role of Antioxidant Supplementation - Daraghmeh, Dala N.; Salameh, Sawsan; Zahdeh, Massa; Ghanem, Rania; Karaman, Rafik (Current Drug Metabolism, 2025)
BackgroundThe female reproductive system is susceptible to oxidative stress, which can interfere with ovulation, menstrual cycles, egg quality, and tubal function, ultimately leading to infertility. Antioxidants might play a crucial role in protecting reproductive health by neutralizing Reactive Oxygen Species (ROS) and preventing cellular damage.ObjectiveTo provide an overview of the research that has been performed on the benefits of antioxidant supplementation for increasing female fertility.MethodsWe conducted a comprehensive search of PubMed, Embase, and Google for full-text, English-language publications between 2000 and 2023 that investigated the relationship between antioxidant supplementation and improvements in female fertility.ResultsAntioxidants have been investigated for their potential to improve fertility outcomes in subfertile women. Antioxidant supplementation shows promise in mitigating these effects by neutralizing excess ROS and restoring balance, leading to improved egg count and fertility outcomes. However, it is important to note that the effectiveness of antioxidant supplementation can vary depending on individual health factors and the specific antioxidants used. Studies suggest that a combination of antioxidants, such as vitamins C and E, selenium, and coenzyme Q10, may be more beneficial than single supplements. Although individual research has shown beneficial correlations between different antioxidant supplementation and female fertility, study repeatability is poor. As a result, further large-scale, well-designed clinical trials are necessary to better understand the precise role and optimal combinations of antioxidants for enhancing fertility in subfertile women.Discussion and ConclusionThis review study offers crucial insights into the complex connection between OS and female reproductive health. It highlights the potential advantages of antioxidant supplements as a preventative strategy. To enhance female fertility outcomes, further research, particularly randomized controlled clinical trials, is needed to determine best practices, identify populations that could benefit the most, and explore innovative antioxidant treatments.
Keywords: oxidative stress